The Territorial Morphology of Comayagua Valley, Honduras - Sosa Caballero, Celina Michelle (2024)
The Comayagua Valley in Honduras, located at coordinates 14˚38'44.73" N and 87˚38'04.90" W, stands out for its altitude of 630 meters above sea level and its dimensions of 52 km in length by 15 km in width, covering an area of 535 km². Despite its economic and connectivity importance, there is a lack of studies addressing its territorial and geomorphological unity and a characterization of its current territorial morphology. The objective of the research is to identify and analyze the shape and natural physical elements that define the Comayagua Valley. To achieve this, Geographic Information Systems tools were used to analyze river layouts, create a digital elevation model, and generate topographic profiles. The main results of this analysis reveal the natural physical elements that shape the valley, which are of vital geo-historical importance for understanding the processes of occupation and land use in the valley.